Formulation of Momordica charantia fruit and Syzygium polyanthum leaf extracts based on in vitro antioxidant and inhibitory activity of α-amylase and α-glucosidase / Muhammad Jihad Sandikapura - Muhammad Jihad, Sandikapura (2018)
Natural products are rich in flavonoids, tannins and other polyphenolics with free radical scavenging potential. Free radicals have been claimed to play an important role in affecting human health by causing several diseases including cancer, hypertension, cardiovascular diseases and diabetes. The primary aim of this study is to extract Momordica charantia fruit, Syzygium polyanthum leaf with maceration, soxhlet, sonication and fresh juice methods, further evaluate the extracts either alone or in combinations for antioxidant (DPPH & FRAP) and enzyme inhibitory effect on α– amylase and α–glucosidase. Other objectives of the study include LC-MS, GC-MS qualitative profiling of extracts and conversion of the best antioxidant and enzyme inhibitory extracts into herbal formulation. Syzygium polyanthum demonstrated better free radical scavenging ability than Momordica charantia. It was observed that the % inhibition of DPPH by S. polyanthum (64.93 %) is comparable to standard quercetin (69.21%). Interestingly the FRAP value of fresh juice of S. polyanthum (69.05 %) was better (p > 0.05) than the quercetin (63.27 %). The fresh juice of S. polyanthum demonstrated predominant inhibitory action against α-amylase (92.21%) and α–glucosidase (96.06 %) than the standard acarbose (88.51 %). Among 28 different combinations of Momordica charantia (MC) and Syzygium polyanthum (SP) extracts in DPPH and FRAP analysis, Maceration MC-Sonication SP (65.35 %; DPPH; p < 0.05) and Soxhlet MC-Fresh Juice SP (59.16 %; FRAP; p < 0.05) have shown significant activities. However, 14 selective combinations were tested for enzyme inhibitory studies and found that Soxhlet MC-Fresh Juice SP (90.86 %; α-amylase; p < 0.05) and Soxhlet MC-Fresh Juice SP (95.52 %; α–glucosidase; p < 0.05) have excellent inhibitory activity against α-amylase and α–glucosidase indicating their ability in controlling postprandial iv hyperglycaemia. GC-MS and LC-MS qualitative analysis identified several polyphenolics, steroids, glycosides, fatty acids and flavonoids in extracts. A combination extract of Soxhlet (MC)-Fresh juice (SP) was formulated as a phytomedicine. The prepared solid herbal formulations (Tablets-550 mg) were evaluated for pharmacopeial tests and found to have good weight variation (554.5 ± 1.45 mg), hardness (56.8 ± 4.3 N), thickness (3.57 ± 0.17 mm), friability (0.72 < 1 %) and disintegration (< 15 min.). In conclusion, the fresh juice of S. polyanthum has superior FRAP scavenging, α-amylase and also α-glucosidase inhibitory activities than standards. Exogenous intake of antioxidants in the form of herbal extracts can help the body scavenge free radicals effectively and can control hyperglycaemia by α-amylase and α-glucosidase inhibition. As these two plants are of dietary importance rich in antioxidants can prevent oxidative damage and improve quality of life in diabetic patients upon inclusion in diet.